LncRNAs associated with multiple sclerosis expressed in the Th1 cell lineage. Issue 12 (8th May 2019) - Hosseini, Aref; Teimuri, Shohreh; Ehsani, Marzieh; Rasa, Seyed Mohammad Mahdi; Etemadifar, Masoud; Nasr Esfahani, Mohammad Hossein; Megraw, Timothy L.; Ghaedi, Kamran
Abstract: Multiple sclerosis (MS) is a type of inflammatory and demyelinating disorder of the central nervous system in which immune‐mediated inflammatory processes are elicited by secreted cytokines from T helper (Th)‐1 and Th17 cells. While some protein‐coding genes expressed in T cell types have established involvement in MS disease progression, little is understood about the roles of long noncoding RNAs (lncRNAs) within the disease landscape. LncRNAs, noncoding RNAs longer than 200 nucleotides, likely control gene expression and function of Th1 cells, and offer the potential to act as therapeutic and biomarker candidates for MS. We identified lncRNAs in Th1 cells linked to MS. Expression levels of candidate lncRNAs and genes were evaluated in 50 MS patients and 25 healthy controls using quantitative real‐time polymerase chain reaction, and their correlations were assessed. LncRNAs encoded by AC007278.2 and IFNG‐AS1‐001 showed significantly higher expression in relapsing Phase MS patients whereas IFNG‐AS1‐003 was elevated in patients in the remitting phase compared with relapsing patients. Collectively, these misregulated lncRNAs may provide valuable tools to understand the relationships between lncRNAs and MS, and possibly other related disorders. Abstract : Three lncRNAs were identified with elevated expression in T helper 1 cells in patients with multiple sclerosis (MS). These lncRNAs appear linked to three genes with involvement in MS, interferon gamma (IFNG), interleukin 18 receptor 1 (IL18R1) and interleukin 18 receptor associated protein (IL18RAP). These lncRNAs are detected in the PBMCs and are potential biomarkers for MS disease.